Experimental investigation on the hysteresis behavior of the wire rope isolators - Balaji, P.; Moussa, L.; Rahman, Muhammad; Vuia, L. (2015)
© 2015, The Korean Society of Mechanical Engineers and Springer-Verlag Berlin Heidelberg. Vibration isolation has been widely applied to filter the external excitation energy and impact forces in building structures and equipment. Wire rope isolator (WRI), a kind of isolator for vibration and shock isolation, shows a better performance in attenuating these forces. WRIs are able to deviate these external forces through their mechanical configuration and high-energy dissipative capabilities. The application of WRI demands knowledge of its behavior and the relation between various geometrical properties and input force. The present work investigates the influence of geometrical parameters, such as wire rope diameter, number of coils, and displacement amplitude on the hysteresis behavior of WRI under quasi-static loading in both vertical and horizontal directions. The hysteresis behavior of different WRIs was evaluated using the calculated parameters from hysteresis force-displacement curves: energy loss ratio (ELR), and effective stiffness. The study indicates that the geometric properties significantly influence the effective stiffness than the energy loss ratio. It is observed that, increased displacement amplitude results in decreased ELR and hence damping capabilities. The study also confirms that the wire rope isolator possesses a good ability in damping through its stiffness and high-energy dissipation capability.